Update on questionnaires for assessing adherence to inhaler devices in respiratory patients. Issue 1 (February 2018) - Plaza, Vicente
Abstract : Purpose of review: It has been estimated that adherence to inhaled medications in patients with asthma and chronic obstructive pulmonary disease (COPD) is around 50%. This low adherence rate increases morbidity and mortality of these disorders. The objective of this review was to update information on main questionnaires used in daily for assessing adherence to inhalers of patients with chronic respiratory diseases. Recent findings: The test of the adherence to inhalers (TAI) is a recently developed and validated 12-item questionnaire to assess adherence to inhalers of aerosolized drugs in patients with asthma or COPD. The instrument can easily identify nonadherence, classify the level of adherence into good, intermediate and poor, and establish three nonadherence behaviour patterns of erratic, deliberate, and unwitting, which are useful for tailoring corrective measures. Summary: Adherence to inhaler devices may be underestimated with the use of validated self-report questionnaires as compared with other more sensitive methods. However, validated self-report questionnaires are more advantageous from a cost-effective perspective in clinical practice. The recently validated TAI is a reliable and homogeneous instrument to identify easily nonadherence and behavioural barriers to the use of inhalers in patients with asthma or COPD.